Kajian Penyakit Layu Fusarium oxysporum pada Tanaman Melon (Cucumis melo L.) Hidroponik di Greenhouse - Susanto, Hendra Ardi; Himawan, Achmad; Kristalisasi, E. Nanik (AGROISTA : Jurnal Agroteknologi, 2023)
This research aims to determine the survey location and symptoms of F. oxysporum wilt on melon plants, how to take samples of plants with symptoms of F. oxysporum wilt, isolate the F. oxysporum fungus in the laboratory, inoculate F. oxysporum fungal spores onto melon plants, incubation period and percentage disease attacks after inoculation of F. oxysporum fungal spores, melon fruit weight and net pattern of melon fruit. This research was carried out at Greenhouse Lahan Indonesia (LI), Maguwoharjo Village, Depok District, Sleman Regency, Yogyakarta Special Region. The research was conducted from April to June 2023. The research used descriptive and quantitative methods to study, describe, explain and describe the objects studied. The research sample plants were 26 plants, namely 5 plants as controls, 21 plants were inoculated with F. oxysporum fungal spores. Location of survey for Fusarium oxysporum wilt symptoms in the Plataran Greenhouse, Selomartani Village, Kalasan District, Sleman Regency, DI Yogyakarta. The survey results showed that there were melon plants that had symptoms of F. oxysporum wilt. The percentage of melon plants affected is 40% of the total plant population. Sampling of melon plant stems with symptoms of F. oxysporum wilting was taken 20 cm from the soil surface and cut to a length of 10 cm. Take 2 plants that experience symptoms of F. oxysporum wilt. Isolation of F. oxysporum fungus using PDA media in a petri dish. Fungal colonies and macroconidia were found which are characteristic of F. oxysporum fungal spores which are shaped like a crescent moon. Inoculation of fungal spores on melon plant stems can cause healthy plants to become sick. On the 10th day there were 2 or 9% of plants showing symptoms of F. oxysporum wilting. There were differences in the weight and net pattern of melon fruit on control plants compared to test plants.